Dermatomyositis as presenting feature of ovarian cancer, treated with neo-adjuvant chemotherapy and interval debulking surgery() - Christie, Alan (Elsevier, 2013)
• Dermatomyositis in ovarian cancer responds to treatment with neo-adjuvant carboplatin and paclitaxel in conjunction with corticosteroids. • Recurrence of dermatomyositis symptoms is often the first sign of relapsed disease. • Prognosis of ovarian cancer in context of dermatomyositis is poor.